Impact Of Electronic Resources In Academic Libraries Of Uttar Pradesh (Journal of Namibian Studies : History Politics Culture, 2023)
Almost every aspect of library services has been significantly and widely impacted by the introduction of information technology. A new generation of libraries with an emphasis on electronic resources has emerged as a result of the quick changes in the library environment. The growing prevalence of Electronic Resources has raised concerns among librarians and staff regarding these resources, their techniques, accessibility, assessment, organisation, and selection. This study has uncovered the current state of Electronic Resources in a few academic libraries located in Uttarakhand. The study also demonstrates the benefits of using Electronic Resources, the challenges users have when trying to access them, and how academic library users view the influence of Electronic Resources. Electronic resources have completely changed library services and operations today. Today, most people can sit down at a computer and conduct online information searches. Ten years ago, most searches took place in libraries and information centres and were mostly tied to scientific and technical bibliographic databases. However, today, these searches are much more popular in the office and at home.